2011
DOI: 10.1186/1756-9966-30-90
|View full text |Cite
|
Sign up to set email alerts
|

Effects of RNA interference-mediated gene silencing of JMJD2A on human breast cancer cell line MDA-MB-231 in vitro

Abstract: Previous data demonstrate that JMJD2A is a cancer-associated gene and may be involved in human breast cancer by demethylation of H3K9me3. The aim of this study was to investigate depressive effects on JMJD2A by transfection with JMJD2A-sepcific siRNA in human breast cancer cell line MDA-MB-231 and effects on cell proliferation, invasion and migration. JMJD2A-specific siRNA was chemically synthesised and transfected into human breast cancer cell line MDA-MB-231. Expression levels of JMJD2A were detected by quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 32 publications
(35 reference statements)
4
41
1
Order By: Relevance
“…KDM4A is overexpressed in many cancer types including prostate, breast, lung and colon cancers and its expression is critical for cell proliferation (Berry et al, 2012; Chu et al, 2014; Cloos et al, 2006; Kim et al, 2012; Li et al, 2012; Li et al, 2011; Mallette and Richard, 2012). We previously reported that by selectively inhibiting KDM4A/4B with a small molecule inhibitor, the LNCaP prostate cancer cells displayed drastic growth retardation and increased apoptosis (Chu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…KDM4A is overexpressed in many cancer types including prostate, breast, lung and colon cancers and its expression is critical for cell proliferation (Berry et al, 2012; Chu et al, 2014; Cloos et al, 2006; Kim et al, 2012; Li et al, 2012; Li et al, 2011; Mallette and Richard, 2012). We previously reported that by selectively inhibiting KDM4A/4B with a small molecule inhibitor, the LNCaP prostate cancer cells displayed drastic growth retardation and increased apoptosis (Chu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that JMJD2A is widely overexpressed in human tissue and cell lines, including breast cancer (Li et al, 2011;Berry et al, 2012), colon cancer (Kim et al, 2012), bladder cancer (Kauffman et al, 2011), and prostate cancer (Shin et al, 2007), although there is rarely evidence about expression of JMJD2A in endometrial carcinoma. We determined JMJD2A expression level in 56 endometrial carcinoma tissues and 20 normal endometrial tissues by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…For example, KDM4A interacts with class I HDACs and retinoblastoma protein (pRb), leading to HDAC-mediated gene inactivation (Gray et al, 2005). Therefore, the KDM4 demethylases are able to function as both transcriptional activators and repressors depending on which complexes they are associated with, and are involved in diverse cellular processes, such as regulation of cell cycle, DNA damage repair and even carcinogenesis (Cloos et al, 2006;Shin & Janknecht, 2007;Li et al, 2011;Berry et al, 2012;Kim et al, 2012;Mallette et al, 2012). An abundance of evidence has demonstrated that overexpression of KDM4 demethylases is involved in numerous cancers.…”
Section: Kdm4: a Subfamily Of Jmjc Domain-containing Protein Demethylmentioning
confidence: 92%